Geochemical Evolution and Groundwater Flow System in Batujajar Groundwater Basin Area, West Java, Indonesia - Suhendar, Rudy; Hadian, M. Sapari Dwi; Muljana, Budi; Setiawan, Taat; Hendarmawan, Hendarmawan (Indonesian Journal on Geoscience, 2020)
DOI:10.17014/ijog.7.1.87-104Batujajar and its surrounding areas, situated in the west of the Bandung Basin, are geologically composed of various Tertiary rock formations with complex fold and fault systems. Springs and drilled wells in sandstone aquifers, tuffaceous sand, and tuffaceous breccias mark the development of their aquifer systems. This study aimed to determine the characteristics of the hydrogeochemistry by analyzing major ions and stable isotopes (18O and 2H) of thirty-four hydrogeological objects. The groundwater flow pattern in this area is controlled by northwest-southeast lineament, as indicated by the emergence of springs along the transition zone between areas with high and low lineament density. In order of dominance, the groundwater facies are as follows:Ca-Mg-HCO3>Ca-HCO3>Ca-Na-Mg-HCO3>Na-Ca-HCO3. Hydrochemical evolutions were detected from the change of cations from Ca2+ to Mg2+ and then Na+, and this is believed to be the product of cation exchange and dissolution of silicate minerals. However, evolutions toward anion changes were not apparent yet, meaning that HCO3- ions still prevail, or in other words the groundwater flow system is local. Nevertheless, the geological and hydrogeochemical analyses, along with the relative compositions of stable isotopes, revealed that the groundwater had three systems, namely shallow, intermediate, and deep groundwater flows; all of which were segmented in three subgroundwater basins (Sub-GWB). Aquifer systems with shallow to intermediate groundwater flow were found in Sub-GWB-A, Sub-GWB-B, and Sub-GWB-C, while the other ones with deep groundwater flow system were identified in Sub-GWB-B and Sub-GWB-C.Fracture system has an important role as a connector between recharge system in hilly areas and discharge system in plain areas.